2012
DOI: 10.1210/jc.2012-1424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Zoledronate on Bone Turnover and Bone Density Persist for at Least Five Years in HIV-Infected Men

Abstract: The effects of two annual 4-mg doses of zoledronate in men persist for at least 5 yr after the second dose. Larger trials assessing the antifracture efficacy of less frequent dosing of zoledronate are justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 19 publications
4
48
0
1
Order By: Relevance
“…It confirms our earlier report 7 that a single 5-mg dose of zoledronate increases BMD above baseline levels and reduces bone turnover markers below baseline levels for at least 5 years. In addition, it suggests that 1-mg and 2.5-mg doses of zoledronate also have long durations of action, such that a 1-mg dose prevents bone loss for 30 months and a 2.5-mg dose for at least 42 months.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It confirms our earlier report 7 that a single 5-mg dose of zoledronate increases BMD above baseline levels and reduces bone turnover markers below baseline levels for at least 5 years. In addition, it suggests that 1-mg and 2.5-mg doses of zoledronate also have long durations of action, such that a 1-mg dose prevents bone loss for 30 months and a 2.5-mg dose for at least 42 months.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence that less frequent administration of the currently recommended 5-mg dose of zoledronate might reduce fracture risk includes data from randomized clinical trials conducted in postmenopausal women, 5 older women in institutional care 6 and men with HIV infection, 7 which have indicated that 4-mg and 5-mg doses of zoledronate produce antiresorptive activity that persists for up to 5 years. A post hoc analysis of the zoledronate phase III trials reported similar reductions in fracture risk after 3 years in response to 3 annual administrations of 5 mg zoledronate and a single baseline administration of 5 mg. 8 …”
mentioning
confidence: 99%
“…In a randomized controlled trial conducted in 43 HIV-infected men with a BMD T-score o À 0.5, increases in lumbar spine and total hip BMD in the treatment and control groups were 8.9% versus 2.6% and 3.8% versus 0.8% after two annual infusions of zoledronic acid, 4 mg. 55 In a 4-year extension of this study, persistence of the effects on BMD and biochemical markers of bone turnover was demonstrated for at least 5 years after the second dose. 56 Significant effects on spine and hip BMD were also reported by Huang et al 57 after a single dose of zoledronic acid, 5 mg, in 30 men with osteopenia or osteoporosis.…”
Section: Pharmacological Interventionsmentioning
confidence: 58%
“…Less frequent dosing schedules (e.g. every 2 years or every 5 years) have been shown to equally suppress bone turnover and preserve BMD, but the efficacy of these alternative dosing strategies in the prevention of fractures has not been established [74,75]. As in the general population, bisphosphonates should not be used in those with hypocalcaemia (both this and vitamin D deficiency should be corrected before bisphosphonate use), renal impairment with an estimated glomerular filtration rate of \35 ml/min, and any hypersensitivity to the product, including any history of uveitis, and should be used with caution in those with osteomalacia.…”
Section: Therapeutic Management Of Osteoporosis In Patients With Hivmentioning
confidence: 99%